El «precio corriente» de las mercancías en el siglo xvii - Beatriz Cárceles de Gea (Casa de Velázquez, 2014)
This paper proposes a review of freedom of trade in the 17th century through a form of legal appeal called súplica. From the rulings on these, or a simple examination of their import, we can see that freedom of trade had become an established provable fact, which moreover was applicable to actual situations that were of too much practical importance and too pressing to be ignored. A legal remedy of appeal against the law not only existed but was effective in that it upheld causes, in this case the freedom demanded by many merchants.